REVIEW OF TRANSMISSION PLANNING APPROACHES IN RESTRUCTURED POWER SYSTEMS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In today’s electric market scenario every country state electricity board has gone for restructuring or more popularly it is termed as deregulated environment of power system. Indian state electricity board has also adopted this newly formed electric market scheme, and divided in generation, transmission and distribution utility. Particularly in this paper transmission system planning in deregulated environment is review from different internationally recognized papers